Effects of bark of Cinnamomum Zeylanicum on hyperglycemia induced oxidative stress and DNA damage in experimental diabetic rats (Funded work) - SAPNEH SHARMA,; ARUN MISHRA, (International Journal of Pharma and Bio Sciences, 2017)
The aim of the study was to evaluate the antihyperglycemic and antioxidative potential of bark of Cinnamomum zeylanicum in alloxan induced diabetic rats and effect on DNA damage. Male rats were divided into four groups comprising of six rats; the third and fourth group were given single intravenous injection of alloxan to develop diabetes while the first and second group received equivalent volume of normal saline and served as control. Two days after alloxan treatment, second and fourth groups were given aqueous suspension of cinnamon bark powder (200mg/kg body weight) dissolved for two weeks. The levels of glutathione peroxidase (GPx), catalase (CAT), superoxide dismutase (SOD), hydrogen peroxide (H2O2), malondialdehyde (MDA) and 4-hydroxynonenal (4HNE) were determined in the liver and the brain. Results showed that levels of H2O2, MDA and 4HNE were significantly increased in the liver and the brain of diabetic rats when compared with control while the activities of GPx, SOD and CAT were significantly decreased when compared with the control group. The results of present study clearly demonstrated significantly high level of DNA single strand and double strand breaks in the liver and the brain of diabetic rats. Our study revealed that cinnamomum zeylanicum bark possesses potent antihyperglycemic and antioxidative effect in experimental diabetic rats. Further studies are required to find out the active compound present in the bark of cinnamon and mechanism of its action for the remedy of hyperglycemia induced disorders.